(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
The approach to this content was inspired by the director’s thinking Russian Vsévolod Meyerhold on theatrical staging as an orchestra and the body of the actor as a musical instrument. This article reports the experience of students stimulated by the investigation of the triad: sound properties, aspects of musicality and theatrical biomechanics of Meyerhold. This period occurred the first half of 2016, as part of a doctoral research developed between 2013 and 2017 by UNIRIO. Among its three practical steps, this article focuses on the second of them: the process of an experience scene idealized as a musical orchestra. This research aims to train the actor-conductor, to be autonomous of his movements and composer of his dramaturgy.